Augmented Brunauer–Emmett–Teller Equation for Water Adsorption on Soils - Chao Zhang (Vadose Zone Journal, 2019)
An augmented Brunauer–Emmett–Teller (BET) equation was developed for describing water adsorption on soils, overcoming the limitation of the original BET equation for describing only isotherms of materials with a homogeneous adsorption surface. The different physicochemical mechanisms underlying water adsorption in soils are synthesized, leading to a unique adsorption sequence dictated by two distinguishable free energy levels. The higher adsorption free energy level reflects the internal (intra-crystalline) surface adsorption, whereas the lower adsorption free energy level reflects the external (particle) surface adsorption. This adsorption energy disparity is provided by the interlamellar energy barrier of van der Waals and electrostatic attractive forces. Consequently, an augmented BET equation was formulated as a combination of the individual BET equations for the internal (intra-crystalline) surface adsorption and external (particle) surface adsorption. The augmented BET equation demonstrates excellent performance in representing measured water adsorption isotherms of a wide suite of silty and clayey soils, validating its applicability. The augmented BET equation excellently predicts the expected dominance of the external particle surface adsorption of the non-polar N adsorption on clay soils, illustrating its ability in separating external and internal surface adsorption. Additionally, the specific surface area estimated by the augmented BET equation matches well the estimation by two independent methods, further confirming the validity of the augmented BET equation.